1986
DOI: 10.1080/01904168609363512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nitrate uptake kinetic parameters across maize inbred lines

Abstract: Eighty-five maize lines were evaluated in a primary screen for differences in uptake rate at 1 mM KNO 3 ; 15 were statistically separable into either "high" or "low" populations. Kinetic parameters were determined by iterative, least-squares regression using a model combining both a saturable and a linear component. Using the inbred B73 as an arbitrary standard, it was determined that the saturable component had a Km of 224 μM and a Vmax of 0.107 μmolNO 3 /mg root dry weight/hr. The ,linear component had a fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 27 publications
3
35
1
Order By: Relevance
“…These kinetics are similar to findings in higher plants (Pace & McClure, 1986;Siddiqi et al, 1990), but differ from previous work on unicellular algae. This paper reports on the nitrate uptake kinetics by natural communities of phytoplankton in a coastal lagoon where nitrate concentrations are generally low, but can reach 70 M seasonally (Picot et al, 1990), and occasional blooms of S. costatum take place (Tournier & Pichot, 1987).…”
Section: Introductionsupporting
confidence: 72%
“…These kinetics are similar to findings in higher plants (Pace & McClure, 1986;Siddiqi et al, 1990), but differ from previous work on unicellular algae. This paper reports on the nitrate uptake kinetics by natural communities of phytoplankton in a coastal lagoon where nitrate concentrations are generally low, but can reach 70 M seasonally (Picot et al, 1990), and occasional blooms of S. costatum take place (Tournier & Pichot, 1987).…”
Section: Introductionsupporting
confidence: 72%
“…At low external ion concentration, ions are absorbed by saturable highaffinity transport systems (HATS), while at high concentrations, nonsaturating low-affinity transport systems (LATS) operate. Such is the case for K + , NH 4 + , NO 3 2 , and ClO 3 2 (a NO 3 2 analog; Kochian and Lucas, 1982;Ullrich et al, 1984;Pace and McClure, 1986;Guy et al, 1988;Siddiqi et al, 1990;Aslam et al, 1992 ] down to 200 mM in tobacco (Nicotiana tabacum; Guy et al, 1988) and for nitrate uptake by barley (Hordeum vulgare) down to 100 mM NO 3 2 (Aslam et al, 1992). These concentrations were the lowest examined by the latter authors.…”
mentioning
confidence: 99%
“…At low [N03-]o, uptake occurs by a high affinity, saturable system, while at high concentrations (>-1 mol m-3 [NO3-]0), uptake may be either saturable (4) or nonsaturable (4,24) according to species or genotype. However, most studies on the kinetic and energetic aspects of NO3-uptake have been confined to the low-concentration system (2, 6 for review) and largely based upon net uptake studies.…”
mentioning
confidence: 99%
“…Studies of net NO3-uptake over a wide range of external NO3-concentrations ([NO3-]o) have revealed that net N03-uptake by plants previously grown with a source of NO3-, (and hence 'induced' for NO3-uptake) is biphasic (4,24). At low [N03-]o, uptake occurs by a high affinity, saturable system, while at high concentrations (>-1 mol m-3 [NO3-]0), uptake may be either saturable (4) or nonsaturable (4,24) according to species or genotype.…”
mentioning
confidence: 99%